2015
DOI: 10.1007/s11062-015-9521-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Injection of Carbon Nanotubes on EEG and Results of a Behavioral Test in Rats

Abstract: We examined the biocompatibility of carbon nanotubes (CNTs) injected i.p. into rats (1 mg/kg body mass) by recording EEG from the frontal and occipital cortex and performing the water maze router test before and after such injection. For EEG, the energy and average power spectral density of wavelet coefficients in the β, α, and θ bands were considered the features. In the water maze router experiment, the distance, time, and speed of rats were investigated as behavioral factors. Comparison of EEG signals befor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…As an ideal carrier for targeted drug delivery, the administration, absorption and transportation of CNT must be carefully investigated to achieve optimum therapeutic effects. The commonly studied routes of CNT administration include oral [ 48 , 49 ] and injection (subcutaneous injection, abdominal injection and intravenous injection) [ 50 , 51 ]. The pH study ( Figure 4 ) shows that LD is easily released at pH 7.4 which is the blood pH, suggesting that the intravenous delivery is a possible way of administration.…”
Section: Resultsmentioning
confidence: 99%
“…As an ideal carrier for targeted drug delivery, the administration, absorption and transportation of CNT must be carefully investigated to achieve optimum therapeutic effects. The commonly studied routes of CNT administration include oral [ 48 , 49 ] and injection (subcutaneous injection, abdominal injection and intravenous injection) [ 50 , 51 ]. The pH study ( Figure 4 ) shows that LD is easily released at pH 7.4 which is the blood pH, suggesting that the intravenous delivery is a possible way of administration.…”
Section: Resultsmentioning
confidence: 99%
“…injection into rats. [ 281 ] It has also been shown that functionalized CNTs caused the release of inflammatory cytokines in the mouse brain, following cortical stereotactic administration. [ 282 ] These observations may be the reason that there have been no clinical trials for the use of CNTs for the treatment of brain glioblastoma.…”
Section: Effects Of Disease On the Bbbmentioning
confidence: 99%
“…For use in drug delivery, it is crucial to demonstrate that CNTs are not toxic. Many studies that did not utilize scanning techniques have intensively studied the toxicity of CNTs ([ 135 , 169 , 190 215 ]. The use of scanning techniques has proven advantageous for toxicity studies [ 85 , 214 , 216 219 ].…”
Section: Nanobioconjugates For Cell Researchesmentioning
confidence: 99%